The integrated treatment of eating disorders, posttraumatic stress disorder, and psychiatric comorbidity: a commentary on the evolution of principles and guidelines - Brewerton, Timothy D. (Frontiers in Psychiatry, 2023)
Psychiatric comorbidity is the norm in the assessment and treatment of eating disorders (EDs), and traumatic events and lifetime PTSD are often major drivers of these challenging complexities. Given that trauma, PTSD, and psychiatric comorbidity significantly influence ED outcomes, it is imperative that these problems be appropriately addressed in ED practice guidelines. The presence of associated psychiatric comorbidity is noted in some but not all sets of existing guidelines, but they mostly do little to address problem other than referring to independent guidelines for other disorders. This disconnect perpetuates a “silo effect,” in which each set of guidelines do not address the complexity of the other comorbidities. Although there are several published practice guidelines for the treatment of EDs, and likewise, there are several published practice guidelines for the treatment of PTSD, none of them specifically address ED+PTSD. The result is a lack of integration between ED and PTSD treatment providers, which often leads to fragmented, incomplete, uncoordinated and ineffective care of severely ill patients with ED+PTSD. This situation can inadvertently promote chronicity and multimorbidity and may be particularly relevant for patients treated in higher levels of care, where prevalence rates of concurrent PTSD reach as high as 50% with many more having subthreshold PTSD. Although there has been some progress in the recognition and treatment of ED+PTSD, recommendations for treating this common comorbidity remain undeveloped, particularly when there are other co-occurring psychiatric disorders, such as mood, anxiety, dissociative, substance use, impulse control, obsessive-compulsive, attention-deficit hyperactivity, and personality disorders, all of which may also be trauma-related. In this commentary, guidelines for assessing and treating patients with ED+PTSD and related comorbidity are critically reviewed. An integrated set of principles used in the treatment planning of PTSD and trauma-related disorders is recommended in the context of intensive ED therapy. These principles and strategies are borrowed from several relevant evidence-based approaches. Evidence suggests that continuing with traditional single-disorder focused, sequential treatment models that do not prioritize integrated, trauma-focused treatment approaches are short-sighted and often inadvertently perpetuate this dangerous multimorbidity. Future ED practice guidelines would do well to address concurrent illness in more depth.